Ultrasound elastography is useful to distinguish acute and chronic deep vein thrombosis. (12th October 2018) - Mumoli, N.; Mastroiacovo, D.; Giorgi‐Pierfranceschi, M.; Pesavento, R.; Mochi, M.; Cei, M.; Pomero, F.; Mazzone, A.; Vitale, J.; Ageno, W.; Dentali, F.
Abstract : Essentials Ultrasound elastography uses tissue deformation to assess the relative quantification of its elasticity. Compression and duplex ultrasonography may be unable to correctly determine the thrombus age. Ultrasound elastography may be useful to distinguish between acute and chronic deep vein thrombosis. The exact determination of the thrombus age could have both therapeutic and prognostic implications. Background: Background: Ultrasound elastography (UE) imaging is a novel sonographic technique that is commonly employed for relative quantification of tissue elasticity. Its applicability to venous thromboembolic events has not yet been fully established; in particular, it is unclear whether this technique may be useful in determining the age of deep vein thrombosis (DVT). Thus, the aim of this study was to assess the role of UE in distinguishing acute from chronic DVT. Methods: Consecutive patients with a first unprovoked acute and chronic (3 months old) DVT of the lower limbs were analyzed. Patients with recurrent DVT or with a suspected recurrence were excluded. The mean elasticity index (EI) values of acute and chronic popliteal and femoral vein thrombosis were compared. The accuracy of the EI in distinguishing acute from chronic DVT was also assessed by measuring the sensitivity, specificity, positive and negative predictive values, and likelihood ratios. Results: One‐hundred and forty‐nine patients (mean age 63.9 years, standard deviation 13.6; 73 males) with acute and chronic DVT were included. The mean EI of acute femoral DVT was higher than that of chronic femoral DVT (5.09 versus 2.46), and the mean EI of acute popliteal DVT was higher than that of chronic popliteal DVT (4.96 versus 2.48). An EI value of > 4 resulted in a sensitivity of 98.9% (95% confidence interval [CI] 93.3–99.9), a specificity of 99.1% (95% CI 94.8–99.9), a positive predictive value of 91.1% (95% CI 77.9–97.1), a negative predictive value of 98.6% (95% CI 91.3–99.9), a positive likelihood ratio of 13.23 (95% CI 93–653) and a negative likelihood ratio of 0.001 (95% CI 0.008–0.05) for acute DVT. Conclusions: UE appears to be a promising technique for distinguishing between acute and chronic DVT. Larger prospective studies are warranted to confirm our preliminary findings.